2021
DOI: 10.3390/molecules26123538
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Reconstituted Collagen Fibers from Chicken Keel Cartilage Depends on Salt Type for Removal of Proteoglycans

Abstract: The aim of the presented research was to obtain reconstituted atelocollagen fibers after extraction from poultry cartilage using the pepsin-acidic method in order to remove telopeptides from the tropocollagen. Firstly, we examined the extraction of collagen from the cartilage extracellular matrix (ECM) after proteoglycans (PG) had been removed by the action of salts, i.e., NaCl or chaotropic MgCl2. Additionally, the effects of the salt type used for PG and hyaluronic acid removal on the properties of self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Tan δ (G′′/G′, defined as tangent loss angle) represented the mechanical loss of polymer in oscillatory motion, reflecting the network structure of gel. The smaller the tan δ value, especially when tan δ < 0.3, the better the gel network structure formed by the protein [ 36 , 37 ]. It was found that all the ultrasonic treatment collagen showed a smaller tan δ value (tan δ < 0.3, Figure 6 C) than that of C0W0m, except for C200W60m (tan δ > 0.3), suggesting that ultrasonic treatment was conducive to the formation of collagen fibril gel network.…”
Section: Resultsmentioning
confidence: 99%
“…Tan δ (G′′/G′, defined as tangent loss angle) represented the mechanical loss of polymer in oscillatory motion, reflecting the network structure of gel. The smaller the tan δ value, especially when tan δ < 0.3, the better the gel network structure formed by the protein [ 36 , 37 ]. It was found that all the ultrasonic treatment collagen showed a smaller tan δ value (tan δ < 0.3, Figure 6 C) than that of C0W0m, except for C200W60m (tan δ > 0.3), suggesting that ultrasonic treatment was conducive to the formation of collagen fibril gel network.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to bones, the slaughter industry also generates huge amounts of cartilage, which can be converted to biochar or activated carbon. This material is structurally different from bone and consists mainly of glycosaminoglycans, proteoglycans, collagen fibres, and elastin [ 27 ]. Thus, cartilage does not contain significant amounts of calcium carbonate or hydroxyapatite, whose thermal decomposition would result in significant porosity in the biochar formed during microwave-assisted pyrolysis.…”
Section: Introductionmentioning
confidence: 99%